Re-thinking Science Education for the Anthropocene - Gilbert, Jane (Palgrave Macmillan Cham, 2023)
This chapter argues that the arrival of the Anthropocene era requires a substantial re-set of science education. It makes a case for re-orienting science education to foreground meta-level understanding of science (looking at it “from above,” in the social/political/cultural/historical context in which it arose) over science’s “content,” its modes of inquiry, and/or its internal social practices. The chapter posits using deconstruction-based approaches to create, not the “used futures” science education is currently entangled with, but the new futures we need. The approaches set out in the chapter would be quite unlike the forms of science education we know today, but, given science’s role in bringing about the Anthropocene era, that is its central point.
Keywords: 47 Language, Communication and Culture; 4702 Cultural Studies; 4 Quality Education